Book Review: Ágoston Berecz, “Empty Signs, Historical Imaginaries: The Entangled Nationalization of Names and Naming in a Late Habsburg Borderland”, New York, Berghahn Books, 2020, 350 p., 14 ill. - RAITA, Florina (Studia Universitatis Babeș-Bolyai Historia, 2021)
The last few years have marked a steady increase in the interest manifested by younger generations of historians in approaching some seemingly exhausted research topics in terms of sources and methods. One of these topics refers to the history of nationalism and nationalities from the multinational empires, for which there is a rich secondary bibliography, as well as multiple primary sources. However, contemporary historians are innovating and enriching the knowledge using some original sources, new methods or perspectives, far more detached from the nationalist fever that characterizes a significant part of the existing researches. Apparently, the names of people, towns and places, as well as the naming processes, do not have a close connection with the history of nationalism, which is why their study was not given much attention. However, Ágoston Berecz, in his most recent book, "Empty Signs, Historical Imaginaries: The Entangled Nationalization of Names and Naming in a Late Habsburg Borderland", addresses the issue of the processes through which the names and denominations had become part of the evolution of national policy and of nationalism in a multiethnic area of Europe: the provinces of Transylvania and Banat, during the nineteenth century. The result of his research is not only a source of useful information for researchers interested in this subject, but also the outcome of the new trend of historiography, characterized by approaching innovative sources and methods which are quite difficult to relate to the history of nationalities, in order to finally bring a fresh perspective upon some much researched topics.